1990
DOI: 10.1295/polymj.22.835
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photo-Induced Reactions of Polymer Radicals in γ-Irradiated Poly(alkyl methacrylate)

Abstract: ABSTRACT:Thermal and photo-induced reactions of radical species generated by y-irradiation of poly(methyl methacrylate) and poly(ethyl methacrylate) have been investigated by means of ESR spectroscopy. The y-irradiation at cryogenic temperature leads to the formation of three major radical species, side chain ---COOC.H 2 • + 1 · -anion radicals and---COOCHC._ 1 H 2 • _ 1 radicals, and main chain -CH-radicals. Cation radicals are immediately converted to the neutral radicals by proton transfer to the polymer mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…In irradiated PEMA, 63 the EPR line of the RA is similar to that mentioned above. No EPR signal was observed that could be assigned to the primary RC, even at 4.2 K. 63 This particle seems to decay rapidly via proton transfer. 62,63 Thus, it seems likely that the observed fluorescence from the PEMA + pTP solution appeared due to the recombination of pTP +• /PEMA −• RIPs.…”
Section: Magnetic Resonance Parameterssupporting
confidence: 74%
“…In irradiated PEMA, 63 the EPR line of the RA is similar to that mentioned above. No EPR signal was observed that could be assigned to the primary RC, even at 4.2 K. 63 This particle seems to decay rapidly via proton transfer. 62,63 Thus, it seems likely that the observed fluorescence from the PEMA + pTP solution appeared due to the recombination of pTP +• /PEMA −• RIPs.…”
Section: Magnetic Resonance Parameterssupporting
confidence: 74%
“…The similar photo-induced radical conversion has been confirmed also for methyl pivalate, C ( C H 3 )3COOCH3, as a model compound of PMMA [43].…”
Section: Thermal and Photo-induced Reactions Of Radicalssupporting
confidence: 68%
“…Figure 10 shows the photo-induced transformation of radical species in irradiated PMMA [43]. Figure 10 shows the photo-induced transformation of radical species in irradiated PMMA [43].…”
Section: Thermal and Photo-induced Reactions Of Radicalsmentioning
confidence: 99%
“…From Figs. 7-8, we found poly(4-hydroxy styrene) has less energy barrier of ionization than poly(acrylic acid) , which coincides with more unstable radical cations of poly(acrylic acid) [14,15]. Figures 9 and 10 shows the decrease of electrons on substituent before and after ionization of poly(4-hydroxy-2,3,5,6-tetra substituted styrene) and poly(α-substituted acrylic acid), respectively.…”
Section: Introductionmentioning
confidence: 70%